1931
DOI: 10.1002/jlac.19314900108
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen in der Reihe der drei‐ und sechsgliedrig‐cyclischen Oxidoverbindungen

Abstract: 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1932
1932
1984
1984

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…7 They reappear again half a century later, with the report by Madelung and Oberwegner that the reaction of an a-chloro ketone with base gave diphenyloxirene. 8 In 1952, Schubach and Franzen reported that 5-decyne (dibutylacetylene) reacted with peroxyethanoic acid (peracetic acid) to give dibutyloxirene.9 All these claims have been shown to have been in error.…”
Section: Introductionmentioning
confidence: 99%
“…7 They reappear again half a century later, with the report by Madelung and Oberwegner that the reaction of an a-chloro ketone with base gave diphenyloxirene. 8 In 1952, Schubach and Franzen reported that 5-decyne (dibutylacetylene) reacted with peroxyethanoic acid (peracetic acid) to give dibutyloxirene.9 All these claims have been shown to have been in error.…”
Section: Introductionmentioning
confidence: 99%
“…is illustrated by the self-condensation of phenacyl bromide (XI), catalyzed by alcoholic sodiunl alkoxides, to form the two geometrical isomers of 4-bromo-l,3-diphenyl-2,3-epoxy-1-butanone (XI I I) (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…These results might tentatively be explained if one assumes that in the trans isomer the approach Treatment of N-benzoylmorpholine (12) with LDA in THF at -78 "C followed by quenching with aqueous NH4C1 resulted in the clean high-yield formation of the ring-opened product (13). Similarly, the reaction of the benzoxazine (14) produced a high yield of enamide (15).…”
Section: Lvj -Hmentioning
confidence: 97%